(3OjhGf CHj JeGes - (3CHh JeGe GdWGFj , CHh JeGe MHjH Hf ChS Hf GdMGQK GdWGFj,J (B231 (3g` s
(3ChdgG (B:s
(3bGd CHhJeGe jeOM eMeO Hf jhSa(B: (3YSi hWf jOfhG Hge hdYdeG hEf JYbH GdCjGe ajge aQHeG s
(3BNQgG (B:s
(3aj eOM GdhGKb HGddg(B: (3heJi jMjW HhUa eLOc hGUa dh cGf Mhd dSGfg GdeLghOG s
(3GdfSNI HgG MhGTs
(3Ydi ghGeTgG JbjjOGJ hJTJed Ydi GdeOGFM hGdCgGLj hGdeQGKjs
(3fSNI QGHYIs
(3HQhGjI GdUhdj s
(3hQO CjVkG JMJ Qbe (B475(3, (B667(3, (B873(3, (B917(3, (B2202(3, (B3247 s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs